Case Report: Clinical Diagnostic Challenges of Hypertrophic Cardiomyopathy (HCM) in a Persian Cat - Fitranda, Mulya; Ryadi, Agus Shafiq; Amalia, Fia; Dion Andiriesta Dewananda; Nururrozi, Alfarisa; Salasia, Siti Isrina Oktavia (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2025)
Hypertrophic Cardiomyopathy (HCM) is a common and clinically significant cardiomyopathies affecting felines characterized by excessive thickening of the left ventricular myocardium and decreased systolic pressure. This report describes the case of a 9-year-old, 4 kg, female Persian cat presented with dyspnea, anorexia, and lethargy. On physical examination, the normal rectal temperature, slight pallor mucous membranes, increases capillary refill time with respiratory distress were observed. Auscultation of the thorax revealed arrhythmia. Blood pressure and mean arterial pressure (MAP) indicated hypertension. Serial blood counts were consistent with anemia, eosinopenia and monocytosis suggesting chronic stress. Thorax radiograph revealed the heart enlargement through vertebral heart scale (VHS) and cardiothoracic ratio (CTR) score measurement. Complementary diagnostic test with biomarker pro-Brain Natriuretic Peptide (proBNP) confirmed the diagnosis of HCM. This case report describes the clinical findings, cardiac evaluation, and HCM diagnosis in a geriatric cat.